APPLYING TEACHER’S SOCIOEMOTIONAL APPROACH TO IMPROVE STUDENTS’ SPEAKING SKILL (Karya Ilmiah Mahasiswa (KIMA), 2024)
This study aims to determine whether the application of the socio- emotional approach can improve students' speaking skills. This study will use quantitative research in the form of an experimental design, this study involves 32 students as a research sample. data collected through tests and questionnaires. the researcher will give a pre-test and post-test, the purpose of the test is to find out the students' speaking skills and also the treatment in 5 meetings to apply the socio- emotional approach. then the researcher will also use a questionnaire to find out students' responses to the socio-emotional approach. The results show that the students' speaking ability in class improves as a consequence of the socio-emotional approach applied to improve students' speaking skills. students become more confident and feel comfortable during speaking practice.   they gradually improve their speaking skills and feel valued even when they make mistakes.